HAKIM PEREMPUAN DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Aziz, Muhammad (Akademika, 2017)
The judicial institution in a country is very strategic and decisive one for being used to resolve all public disputes and punish those who violate the law in accordance with the emering rules. This judicial institution is needed in an effort to answer and solve all social problems along with the development and the dynamics in the community. A judge is an authority aimed at resolving the various conflicts and creating justice for the community, and judges are leading actors in solving the problems. Therefore judges in acting and taking decisions must be based on so-called ijtihad. The phenomenon of women's involvement as judges in administering judicial power in the Religious Courts has undergone several phases of change. This condition is strongly influenced by the striking discrepancy of fiqh viewpoints about the religious (syar'i) legalityÂ  in looking at women in the public sphere, especially in the judiciary. One of the reasons of Muslim scholars in questioning the female judges is due to their duties and responsibilities. On this stand, the Muslim scholars, thingkers and mujtahid have their own points of view that are different from one another. This refusal does not mean ignoring the judicial institution, but rather they consider it fardhu kifayah. Therefore, what is to be revealed in this study is the Islamic law and Indonesian positive law perspectives about female judges. This study concludes that the study of female judges in the perspectives of Islamic law is polarized on several permitting and prohibiting poles and the ones permitting women to serve as judges are only in their involvement in civil cases not in criminal ones. While based on the perspective of Indonesian positive law the female judges are a must in the legal treasures in Indonesia.